Esperança de vida em mulheres diagnosticadas com câncer de mama submetidas à mastectomia - Mendes, Cláudia Rayanna Silva (2017)
When experiencing the diagnosis of breast cancer and undergoing a mastectomy, women begin a new path in their lives, ranging from accepting the disease to readapting and post-mastectomy psychosocial adjustments. Hope, motivation and energy are essential to encourage these women to undergo the treatment and adapt to the changes arising from breast cancer as well as improve their physical and mental health. In this context, the general objective was to analyze the levels of hope of women with breast cancer in the pre- and postoperative periods of mastectomy, through the Herth Hope Index (HHI). This is a descriptive and prospective longitudinal study conducted with women diagnosed with breast cancer admitted to the surgical clinic sector at the Haroldo Juaçaba Hospital (Ceará Cancer Institute), located in Fortaleza, Ceará, Brazil, for mastectomy. Data collection took place from July to November 2016, through individualized interview, using a form to collect sociodemographic and clinical data and application of the Herth Hope Index (HHI) in two moments, in the pre-mastectomy and post-mastectomy periods. Data were tabulated and entered in an electronic database made in Microsoft Excel 2010 and analyzed through descriptive statistics (frequency, mean, and standard deviation), based on pertinent literature and analytical statistics, using the Statistical Package for the Social Sciences (SPSS for Windows) software, version 20.0. Bioethical principles established by Resolution 466/2012 of the National Health Council were followed when carrying out the study. The project was sent to the Brazil Platform and performed with the approval of the Ethics Committee, according to protocol No. 1,552,285. Regarding the levels of hope, there was a maximum value of 48 points, both in the pre- and postoperative periods; a minimum value of 29 points, in the pre- and postoperative periods; and an overall mean of 40.6 (±0.4) points in the preoperative period and 41.9 (±0.4) points in the postoperative period, thus demonstrating high levels of hope in the preoperative period and increased hope after performing the surgical procedure. The only sociodemographic variable that presented a significant association with the levels of hope was religion, whose presence contributed to the high levels, both in the pre- and postoperative periods. As for the other variables, it was found that pain and family-related hope were associated with lower levels of hope in both the pre- and postoperative periods, while knowledge, religion-related hope and the anatomical location in a single breast surgery positively influenced the levels of hope. It was also verified the possibility of predicting the postoperative score only by using the preoperative score, in 76% of the cases, having as main factor to explain the hope in the postoperative the hope in the preoperative period and, although selective lymphadenectomy and family-related hope have explanatory effect, there is a minimal impact when compared to the influence exerted by the preoperative score. Findings of the present study enable to conclude that women diagnosed with breast cancer submitted to surgical treatment had hope in the preoperative period, evolving with increased levels of hope in the postoperative period.